Clinical Practice Guidelines of Chinese Medicine Rehabilitation for Ischemic Stroke （Cerebral Infarction）Working Group of Clinical Practice Guidelines of Chinese Medicine Rehabilitation for Ischemic Stroke (Cerebral Infarction) - Working Group of Clinical Practice Guidelines of Chinese Medicine Rehabilitation for Ischemic Stroke (Cerebral Infarction) (康复学报)
Ischemic stroke (cerebral infarction) is a common clinical disease of ischemic necrosis or softening of localized brain tissue, which belongs to "stroke disease" in traditional Chinese medicine (TCM). In recent years, its incidence rate has gradually increased, the age of onset tends to be younger, and seriously affects the quality of life of patients with cerebral infarction. TCM rehabilitation is one of the effective methods to improve clinical symptoms and prevent recurrence. The clinical practice guideline of TCM rehabilitation of cerebral infarction based on the concept and method of evidence-based medicine is of great significance, which is helpful to standardize the operation technique of TCM rehabilitation of cerebral infarction and obtain better curative effect. This guideline standardizes the diagnosis and rehabilitation treatment of cerebral infarction in terms of scope, terminology, diagnosis of TCM and western medicine, rehabilitation assessment, TCM rehabilitation treatment and nursing, in order to provide guidance and reference for clinicians or rehabilitation doctors in diagnosis and treatment. ① Diagnosis: it is divided into TCM diagnosis and western medicine diagnosis, TCM diagnosis includes disease differentiation and syndrome differentiation (meridian involved style and viscera involved style), and western medicine diagnosis includes diagnosis basis, clinical stage and quantitative classification of clinical condition. ② Rehabilitation assessment: it mainly includes the assessment of neurological impairment, motor function, balance function, speech function, swallowing function, cognitive function, psychological assessment and quality of life. ③ Rehabilitation treatment of traditional Chinese medicine (TCM): it mainly stipulates the diagnosis and treatment technologies of traditional Chinese medicine treatment, acupuncture therapy, massage therapy, traditional functional methods, rehabilitation treatment and nursing in the ultra early stage, acute stage, recovery stage and sequelae stage of cerebral infarction. The guideline could provide guidance for the rehabilitation treatment of cerebral infarction in different levels and kinds of rehabilitation institutions, traditional Chinese medicine hospitals or general hospitals. It has good clinical applicability and effectiveness.